Potential Regulatory Roles of GRK2 in Endothelial Cell Activity and Pathological Angiogenesis - Kuai, Jiajie; Han, Chenchen; Wei, Wei (Frontiers in Immunology, 2021)
G protein-coupled receptor (GPCR) kinase 2 (GRK2) is an integrative node in many signaling network cascades. Emerging evidence indicates that GRK2 can interact with a large number of GPCRs and non-GPCR substrates in both kinase-dependent and -independent modes. Some of these pathways are associated with endothelial cell (EC) activity. The active state of ECs is a pivotal factor in angiogenesis. The occurrence and development of some inflammation-related diseases are accompanied by pathological angiogenesis, but there remains a lack of effective targeted treatments. Alterations in the expression and/or localization of GRK2 have been identified in several types of diseases and have been demonstrated to regulate the angiogenesis process in these diseases. GRK2 as a target may be a promising candidate for anti-angiogenesis therapy.